Domestic and International Advances and Challenges in Early Diagnosis of Prediabetes with Integrated Chinese and Western Medicine - PENG Hongye, JING Yanan, LIU Dianchun, WANG Ying, XUE Xue, LU Chunli (Zhongguo quanke yixue, 2025)
Prediabetes is a condition characterized by impaired fasting glucose, impaired glucose tolerance, or a combination of both, which is classified under the category of "Pi Dan" in Traditional Chinese Medicine (TCM). With the changes in modern lifestyles, the prevalence of prediabetes is continuously rising, carrying a risk comparable to diabetes prognosis. Therefore, timely diagnosis and early intervention are crucial. This article reviewed the origins and definitions of prediabetes from both TCM and modern medical perspectives, revealing that TCM had already recognized "Pi Dan" as early as the composition of the "SuWen". With the development of evidence-based medicine and the implementation of standardized clinical research, China has gradually established the standardized clinical practice guidelines for prediabetes with TCM characteristics. Regarding diagnosis, diagnostic indicators and thresholds for monitoring blood glucose levels, various non-invasive integrated TCM and modern medical diagnostic methods, including TCM syndrome diagnosis, integrated TCM and Western medicine diagnostic models, disease risk scoring models, biomarkers, and wearable devices, have been continuously improved. However, its primary focus lies in diabetes prevention rather than the early detection and screening of prediabetes. Besides, 1-hour plasma glucose may be a new outcome for prediabetes diagnosis or identifying high-risk diabetes populations in the future. However, further research is required to validate its broader application. Addressing the challenges of dynamic diagnostic standards, complex screening processes, atypical clinical symptoms, and low disease awareness during early prediabetes diagnosis, it is imperative to continuously update and refine diagnostic standards. The integration of digital health management and wearable devices should be promoted to fully capitalize on TCM strengths in constructingt disease diagnostic models that combine TCM macro manifestations and omics microdata for prediabetes. Simplified and expedited integrated TCM and modern medical screening methods can facilitate early screening, early diagnosis, early intervention, and early recovery for prediabetes.